From Our Own Correspondent: teachers' professional learning in the Republic of Ireland context. Issue 1 (2nd January 2019) - Broderick, Nicola
ABSTRACT: Teacher professional learning will become a legislative requirement for all Irish teachers in 2020. This paper discusses likely future developments of this new policy, Cosán (TCI), 2016), within the current educational context. Similar to other international mandatory professional learning policies, Cosán has potential to enhance teacher professional learning but many contentious factors remain: contestation between the policy as a mode of accreditation or a vehicle for public accountability; the necessity to provide evidence of professional learning to retain teacher registration; allocation of funding and time for professional learning; and evaluation of professional learning opportunities. In order for the positive effects of Cosán to be realised, these key issues need to be addressed.